IMPROVING STUDENTS’ READING COMPREHENSION SKILL USING HERRINGBONE TECHNIQUE AT MTS AL-FATAH BADAS - Ary Setya Budhi Ningrum; Ika Widyawati (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2015)
Reading is a factor of great importance in the individual development and the most important activity at school. In MTs Al-Fatah, however, the students’ reading comprehension score was still low. To overcome the problem, the herringbone technique was implemented to improve the students’ reading comprehension in narrative text. Classroom Action Research (CAR) was carried out in this study. This research consists of two cycles. Each cycle consists of two meetings. In cycle 1, the students’ score in reading comprehension has not reached the criteria of success yet. There were only 66,7% (8 out of 24 students) who passed the criteria of success. So, the researchers revised the plan and continued to the next cycle. In cycle 2, the average score of students was improving. All of students get good score and none get poor score. To sum up, the herringbone technique applied for the eighth grade of MTs al-Fatah Badas was qualified to be able to improve the students’ achievement in reading narrative text